Applied GIS and remote sensing in planning routes for irrigation canal systems (The case of Matuno-Santo Domingo communal irrigation project in Nueva Vizcaya, Philippines) - Ramos, Ian Dominic S. (2003)
This study presents a method in planning for irrigation canal routes using modern earth data acquisition and spatial analysis technologies - Remote Sensing (RS) and Geographic Information Systems (GIS). The method is specially proposed as an alternative to the long, tedious, costly, and sometimes dangerous conventional way of locating canal routes by ground survey. The process involved in conventional ground surveying for canal route planning were analyzed for stages where information about geographic location play crucial roles but are hampered by instrument and environmental constraints. These stages are best served by utilizing RS and GIS technologies because of their capabilities in acquiring data from great distances and from integrating georeferenced phenomena. The Matuno-Santo Domingo Communal Irrigation Project in Bambang, Nueva Vizcaya provided an interesting case to apply the methodology. Available maps and other survey data from the National Irrigation Administration-Nueva Vizcaya Provincial Irrigation Office (NAI-NVPIO) project were converted to digital format and organized into a GIS environment in Arcview, while a Landsat-TM image of the study area was classified to come up with a comprehensive landuse/landcover map. A digital elevation model (DEM) was created from teh digitized contour lines and spot heights. The identified and geo-referenced water sources were overlaid on the DEM, and together with information about water discharge rates, soil types, cadastral boundaries, and the cropping calendar of the Matuno-Santo Domingo area, this facilitated the delineation of possible canal routes and approximation of route costs.
Using RS/GIS techniques, the canal route indentification process took 60 days to complete. Its output map yielded 53.56 km irrigation network over 1,090.75 hectares of irrigable areas across the 10,084.21 hectares of the study area. The conventional method of canal route identification by ground survey was approximated by the NIA-NVPIO project team to take 273 days for only 1,227.27 hectares of surveyed land. This would cover 31.91 km of canal network for 520 hectares of irrigable areas. An overlay of the maps for the two methods showed upstream agricultural areas that the conventional method had missed. It also showed the need to construct additional farm ditches to distribute water to the poorly irrigated portions of the irrigable lands.
The subjects of comparison between the conventional and RS/GIS-assisted canal route planning were identified, and revolved around the extent of mapped area, completeness of identified agricultural areas, distribution of canal system on these areas, perpendicularity of irrigation canals, speed, cost, exposure to work hazards and delay factors.
Thesis (MS Remote Sensing)--University of the Philippines Diliman)
Keywords: Irrigation canals and flumes--Philippines--Bambang (Nueva Vizcaya).; Irrigation--Philippines--Bambang (Nueva Vizcaya)--Remote sensing; Geographic information systems--Philippines--Bambang (Nueva Vizcaya).; Irrigation projects--Philippines--Bambang (Nueva Vizcaya).; Remote sensing--Philippines--Bambang (Nueva Vizcaya).; Matuno-Santo Domingo Communal Irrigation Project